THE URGENCY OF INSTILLING THE CREED OF TAWHID TO STUDENTS: A Study of Luqman Al-Hakim's Advice in the Book of Tafsir As Sa'di - Hamzah, Muhammad Habibi; Shalihah , Raadliyatush (Sekolah Tinggi Ilmu Tarbiyah (STIT) Al-Ishlah Bondowoso, 2022)
Maintaining the purity of the faith of the younger generation of Muslims is a shared responsibility, especially parents and teachers. In this modern era, the exchange of information is so easy to find without any restrictions. So re-teaching the holy Qur'an to the younger generation of Muslims is a solution. Where one third of the Qur'an conveys about faith. Among the verses of the Qur'an that talk about faith is the story of Lukman Al-Hakim's advice to his son in Surah Lukman. So this research is a qualitative study of literature on the book of tafsir As-Sa'di. In order to explore the meaning contained in Lukman's advice to his son. With the hope that it can be an inspiration for parents and teachers to concentrate more in instilling the values of true faith to the younger generation of Muslims. Keywords: Akidah, tawhid, Lukman Al-Hakim, tafsir As-Sa'di.